Encounter, transformation and identity : peoples of the western Cameroon borderlands, 1891-2000 - Fowler, Ian; Fanso, Verkijika G.; Njeuma, M. Z., 1940-2010 (Cameroon studies, 2009)
Bringing together key historical and innovative ethnographic materials on the peoples of the South-West Province of Cameroon and the Nigerian borderlands, this volume presents critical and analytical approaches to the production of ethnic, political, religious, and gendered identities in the region. The contributors examine a range of issues relating to identity, including first encounters and conflict as well as global networking, trans-national families, enculturation, gender, resistance, and death. In addition to a number of very striking illustrations of ethnographic and material culture.